Dynamics of monetary and multidimensional poverty in Cameroon - Andrianarison, F; Housseini, B; Oldiges, C (Oxford Poverty and Human Development Initiative, 2022)
Cameroon has witnessed substantial economic growth in the new millennium, while pov- erty reduction has been limited and inequality has worsened. In this context, this paper in- vestigates the different facets of poverty in Cameroon, the factors affecting them, and policy options to tackle poverty and achieve inclusive and sustainable development. We apply two prominent poverty measurement methods (Alkire–Foster and Foster–Greer–Thorbecke) to a series of household consumption and living standards (ECAM) surveys and Demographic and Health Surveys (DHS) collected between 2001 and 2018, and perform various empirical analyses to elucidate poverty dynamics and features. Our results indicate that both mone- tary and multidimensional poverty decreased in Cameroon between 2001 and 2018, albeit slowly and to varying degrees across the different demographic, socio-economic, and spatial groups of the population. We find that the proportion of multidimensional poor people was always higher than the proportion of the monetary poor. At the same time, multidimen- sional poverty has reduced much faster than monetary poverty at the national level. Lastly, we find that higher levels of poverty in Cameroon are strongly associated with rural liveli- hoods, large family size, less education, employment in agriculture, and the northern regions of the country. Our microeconomic analysis is complemented with a review of structural factors affecting poverty at the macro level. We point out the need to accelerate the struc- tural transformation of the Cameroonian economy to reduce inequalities across the different regions and subgroups of the population and expand economic opportunities for the youth to achieve the demographic dividend.